First reports of nasal and traumatic myiasis infection in endangered Przewalski's horses (Equus ferus przewalskii). (August 2019) - Yan, Liping; Zhang, Ming; Tang, Liping; Ente, Make; Ma, Xinping; Chu, Hongjun; Li, Kai; Hu, Defu; Zhang, Dong
Abstract: Myiasis has great economic and medical importance. However, myiasis in wildlife that is caused by oestroid flies is relatively rarely recorded compared with that in humans and domestic animals. Recently, during our research on the conservation of Przewalski's horse (PH), we observed two new records of oestroid flies parasitizing wildlife in China. The first is the horse nasal bot fly, Rhinoestrus sp. (Diptera: Oestridae), found in a dead PH from Kalamaili Nature Reserve. One morphotype ( R. purpureus -like) was identified. The second is the Wohlfahrt's wound myiasis fly, Wohlfahrtia magnifica (Schiner, 1862) (Diptera: Sarcophagidae), which was collected from an open wound of a PH in the Wild Horse Breeding Research Centre. These observations extend the records of known hosts of these two oestroid myiasis agents. To the knowledge of the authors, infestation by Rhinoestrus and Wohlfahrtia larvae causing myiasis in wildlife has not been reported in China previously. Graphical abstract: Image 1 Highlights: First report of Rhinoestrus sp . and Wohlfahrtia magnifica parasitizing Przewalski's horses. Infestation by Rhinoestrus and Wohlfahrtia larvae causing myiasis in wildlife has not been reported in China previously. This study will enrich the epidemiological data of myiasis infection of wildlife in China.